THE BASIC PRINCIPLES OF TEACHING HISTORY OF ENGLISH-SPEAKING COUNTRIES (Modern education and development, 2025)
This article explores the fundamental principles of teaching the history of English-speaking countries. It delves into the importance of such education, analyzes existing literature on effective teaching methods, presents results from practical applications, discusses implications, and provides conclusions and suggestions for educators.